2003
DOI: 10.1074/jbc.m208955200
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal End of Bax Contains a Mitochondrial-targeting Signal

Abstract: The translocation of Bax ␣, a pro-apoptotic member of the BCL-2 family from the cytosol to mitochondria, is a central event of the apoptotic program. We report here that the N-terminal (NT) end of Bax ␣, which contains its first ␣ helix (⌯␣1), is a functional mitochondrial-addressing signal both in mammals and in yeast. Similar results were obtained with a newly described variant of Bax called Bax , which lacks the first 20 amino acids of Bax ␣ and is constitutively associated with mitochondria. Deletion of ⌯␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
132
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(142 citation statements)
references
References 31 publications
6
132
4
Order By: Relevance
“…12 Numerous study have shown that in a simple cell-free assay using isolated mitochondria and purified or in vitro translated (IVT) Bax could accurately reproduce early events of the Bax-induced permeabilization of the mitochondria. 10,[13][14][15] In order to elucidate the receptors involved in Bax association with mitochondria, we subjected isolated mitochondria to a mild proteolysis by trypsin using a protocol described earlier for the identification of components of the outer membrane import machinery. 16 Isolated rat liver mitochondria were treated with 0, 5 or 50 mg/ml trypsin for 30 min at 41C (see Materials and Methods) before immunoblot analyses of selected mitochondrial proteins.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…12 Numerous study have shown that in a simple cell-free assay using isolated mitochondria and purified or in vitro translated (IVT) Bax could accurately reproduce early events of the Bax-induced permeabilization of the mitochondria. 10,[13][14][15] In order to elucidate the receptors involved in Bax association with mitochondria, we subjected isolated mitochondria to a mild proteolysis by trypsin using a protocol described earlier for the identification of components of the outer membrane import machinery. 16 Isolated rat liver mitochondria were treated with 0, 5 or 50 mg/ml trypsin for 30 min at 41C (see Materials and Methods) before immunoblot analyses of selected mitochondrial proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Ha1 and Ha9). 9,10 With respect to the localization of these helices, the Ha1 of Bax was fused at the N-T of the RFP to form a Ha1-RFP construct while Ha9 and a Ha9 mutant containing a single deletion of S184 9 were fused to the C-T of RFP to form the RFP-Ha9 and RFP-Ha9 DS184 constructs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations